URGENSI REKONSTRUKSI MAHKAMAH KONSTITUSI DALAM MEMBERIKAN PERTIMBANGAN KEBIJAKAN HUKUM TERBUKA (OPEN LEGAL POLICY) - Fauzani, Muhammad Addi; Rohman, Fandi Nur (Penerbit Universitas Atma Jaya Yogyakarta, 2019)
This research has two problem formulations, First, how the Constitutional Court's construction in giving consideration to